Analysis of Research Data Management Policies in Health Sciences at Thai Universities - Wongkaew, Chatree; Sripromsuk, Nongyao; Sapsomboon, Bordin; Wipawin, Namtip (Journal of The Royal Thai Army Nurses, 2025)
This research aimed to analyze and compare research data management policies in health sciences among ten distinguished Thai universities with outstanding research output during 2021-2023. The study employed documentary research methodology through systematic data collection from domestic academic databases and institutional websites. Data analysis was conducted using the knowledge management theoretical framework and FAIR Data Principles. The findings revealed that at the national level, the National Research Council of Thailand and the Thai Industrial Standards Institute have established Trustworthy Digital Repository standards as criteria for data storage system governance; however, a comprehensive national data management policy has yet to be formulated. At the institutional level, all universities possessed comprehensive foundational policies encompassing research governance, ethics, and intellectual property management. Nevertheless, none of the institutions had established specific, comprehensive research data management policies, with practical guidelines remaining dispersed across faculty and departmental levels. Analysis through the knowledge management theoretical lens revealed asymmetrical development across constituent components, while assessment according to FAIR principles demonstrated limitations across all dimensions, particularly in data reusability capabilities. Furthermore, significant disparities were observed between Bangkok-based and regional universities regarding both resource allocation and infrastructure development. These findings underscore the imperative for developing systematic research data management policies that conform to international standards and best practices.